A process for producing high oleic content liquid palm oil fraction - Lai, Oi Ming; Tan, Chin Ping; Mat Dian, Noor Lida Habi; Mat Sahri, Miskandar (2013)
A process for producing high oleic contentliquid palm oil fraction wherein the process includes subjecting substantially moisture-free palm oil to heat resulting in molten palm oil, lowering the temperature adding catalyst uinto the molten palm oil to initiate directed interesterification reaction, subjecting the oil-catalyst mixture to react at directed interesterification temperature, deactivating the catalyst, removing the catalyst from the directed interesterified palm oil, purifying the catalyst-free directed interesterified palm oil, purifying the catalyst-free directed interesterified palm oil, subjecting the purified directed interesterified palm oil, crystallizing the molten directed interesterified palm oil form high oleic content liquid palm olein and high palmitic content solid stearin fractions and seperating the high palmitic content stearin solid crystals resulting in high oleic content liquid palm oil fraction.